2020
DOI: 10.1371/journal.pone.0244489
|View full text |Cite
|
Sign up to set email alerts
|

Consistent patterns in 16S and 18S microbial diversity from the shells of the common and widespread red-eared slider turtle (Trachemys scripta)

Abstract: Microbial communities associated with freshwater aquatic habitats and resident species are both critical to and indicative of ecosystem status and organismal health. External surfaces of turtle shells readily accumulate microbial growth and could carry representation of habitat-wide microbial diversity, since they are in regular contact with multiple elements of freshwater environments. Yet, microbial diversity residing on freshwater turtle shells is poorly understood. We applied 16S and 18S metabarcoding to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Compared to the carapace, the skin of the neck and flippers (sampled in this study) is prone to higher mechanical disturbance caused by the turtle's movements. Parks et al (2020) reported a higher diversity and richness of microbial communities on the freshwater turtles' carapace in comparison to the plastron, and provide the movement of the turtles as one of the possible explanations. Furthermore, Blasi et al (2022) reported significant differences between microbial communities of differently positioned carapace scutes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Compared to the carapace, the skin of the neck and flippers (sampled in this study) is prone to higher mechanical disturbance caused by the turtle's movements. Parks et al (2020) reported a higher diversity and richness of microbial communities on the freshwater turtles' carapace in comparison to the plastron, and provide the movement of the turtles as one of the possible explanations. Furthermore, Blasi et al (2022) reported significant differences between microbial communities of differently positioned carapace scutes.…”
Section: Discussionmentioning
confidence: 91%
“…However, very little is known about the epimicrobiomes of reptiles, especially turtles, including terrestrial, freshwater, and marine species. Recently, there have been studies on external microbial communities of freshwater turtles (Trachemys scripta, Pseudemys concinna, and Emydura macquarii krefftii) that identified major microbial components of eukaryotic, bacterial and archaeal surface communities and showed that turtles' microbiotas differ between body parts and between animals and their environment (McKnight et al, 2020;Parks et al, 2020). New knowledge about the functional and phylogenetic composition of epimicrobiomes of different species improves our understanding of the relationships between the host, its microbial flora, and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…There is no current literature citing the use of next generation sequencing on skin samples in sea turtles. However, there are studies that investigated the skin and shell microbiota of freshwater turtles such as the red-eared slider (Trachemys scripta) and the Krefft's river turtle (Emydura macquarii krefftii) [57,58]. These studies suggest that there are unique microbiota located on different parts of the skin, such as the head and the shell with and without algae [57,58].…”
Section: Skin and Shellmentioning
confidence: 99%
“…However, there are studies that investigated the skin and shell microbiota of freshwater turtles such as the red-eared slider (Trachemys scripta) and the Krefft's river turtle (Emydura macquarii krefftii) [57,58]. These studies suggest that there are unique microbiota located on different parts of the skin, such as the head and the shell with and without algae [57,58]. Microbiota located on the skin, plastron, and carapace of sea turtles is an area in need of investigation.…”
Section: Skin and Shellmentioning
confidence: 99%
“…However, very little is known about the epimicrobiomes of reptiles, especially turtles, including terrestrial, freshwater, and marine species. Recently, there have been studies on external microbial communities of freshwater turtles ( Trachemys scripta, Pseudemys concinna and Emydura macquarii krefftii ) that identified major microbial components of eukaryotic and prokaryotic surface communities and showed that turtles’ microbiotas differ between body parts and between animals and their environment (McKnight et al, 2020; Parks et al, 2020). New knowledge about the functional and phylogenetic composition of epimicrobiomes of different species improves our understanding of the relationships between the host, its microbial flora, and the environment.…”
Section: Introductionmentioning
confidence: 99%